Mapping worldwide research on the Internet of Things during 2011-2016 - Erfanmanesh, Mohammadamin; Abrizah, Abdullah (Emerald, 2018)
Purpose: The Internet of Things (IoT) has attracted wide attention from researchers to address the potential of this technology in various industries recently. This study aims to investigate different characteristics of worldwide research on the IoT using bibliometrics, network analysis and altmetrics. Growth of the literature, publication types, languages, publication countries and research subjects are addressed. The scientific and social impact of the journal articles has also been examined using citation and altmetrics scores. Design/methodology/approach: The Scopus database was searched for articles indexed under the terms “Internet of Thing*” or “IoT” or “Internet of Everything*” or “Web of Thing*”, and a total of 13,725 articles from 2011 to 2016 were retrieved and analysed. Findings: There was a continuous increase in the number of publications per year over the period, with a 6.7-fold rise in the number of publications, with the highest share of research output (4,989) published in 2016. Contribution of authors at the micro, meso and macro levels was analysed. About 89 per cent of total publications were the result of collaborative efforts, and Asia-Pacific was responsible for almost 53 per cent of world scientific production of IoT literature. Generally, the IoT research are found in publications concentrating on computer networks and communications, electrical and electronic engineering and computer science applications. The results also showed that the presence of IoT research on the social web is still low, with 6.8 per cent of total publications presenting some altmetric activity. Research limitations/implications: The work reported is limited to only Scopus-indexed publications. While the search methodology aimed to be as inclusive as possible, it may not have captured all scholarly research output in the IoT world. Practical implications: The findings of this study may help researchers understand the performance of IoT research from across the world and suggest directions for further research. Originality/value: This paper reviews the literature of the IoT in past five years using rigorous bibliometric, altmetric and network analysis tools.